2021
DOI: 10.1002/jimd.12372
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of peripheral neuropathy in disorders of the mitochondrial trifunctional protein

Abstract: Peripheral neuropathy is a known irreversible long-term complication of longchain 3-hydroxyacyl-CoA dehydrogenase deficiency (LCHADD) and mitochondrial trifunctional protein deficiency (MTPD), two inherited disorders of mitochondrial long-chain fatty acid oxidation. The underlying pathophysiology of neuropathy is still not fully understood. We report electrophysiological studies and neurological findings in a series of 8 LCHAD-deficient and 11 MTP-deficient patients. The median age at time of the study was 8.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 22 publications
(84 reference statements)
2
44
0
Order By: Relevance
“…18 A newly published study on patients with MTP deficiency and neuropathy describes neuropathy as the only presenting symptom in four children. 10 However, variants in the HADHA gene were the likely cause of the metabolic disorder in these cases. On the other hand, in the cases presented in the latter study, the long-lasting episodes of weakness were reversible, mimicking the findings in our three adult patients.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…18 A newly published study on patients with MTP deficiency and neuropathy describes neuropathy as the only presenting symptom in four children. 10 However, variants in the HADHA gene were the likely cause of the metabolic disorder in these cases. On the other hand, in the cases presented in the latter study, the long-lasting episodes of weakness were reversible, mimicking the findings in our three adult patients.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, Nadjar and colleagues described four MTP cases with a new phenotype with adult‐onset ataxia and sensory ganglionopathy, but these were preceded by rhabdomyolysis in childhood in all cases 18 . A newly published study on patients with MTP deficiency and neuropathy describes neuropathy as the only presenting symptom in four children 10 . However, variants in the HADHA gene were the likely cause of the metabolic disorder in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that C7 might be more efficient than C8 in this respect. Peripheral neuropathy of LCHADD and MTPD is described as axonal neuropathy with possible secondary demyelination [ 56 ]. Our previous study demonstrated increased HEX levels in LCHADD fibroblasts [ 19 ]; if disruption of sphingolipid metabolic flux were to occur also in vivo, it would be indicative of a possible derangement of proper myelination, thereby affecting neurological function [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,3 The neuropathic phenotype is heterogeneous comprising isolated sensory, 4,5 isolated motor 1 and sensorimotor forms. 1 Neuropathy is usually considered irreversible. 3 We recently outlined the clinical spectrum of peripheral neuropathy in a cohort of 8 LCHAD deficient and 11 MTP-deficient patients.…”
Section: Introductionmentioning
confidence: 99%